Parkett : The Parkett series with contemporary artists (Zürich : Parkett-Verlag, 2017)
Table of Content Aural Traditions: The Art of Jason Moran by Naomi Beckwith Cao Fei The Chinese City Between Dream World and Catastrophe by Tom McDonough Cao Fei’s Avatars and Antiheroes by Hou Hanru Cao Fei, Performance Without Transcendence by Jiayun Zhuang Lynette Yiadom-Boakye The Quiet Bohemia of Lynette Yiadom-Boakye’s Paintings by Rizvana Bradley Levitating Blackness: Lynette Yiadom-Boakye’s Right to Opacity by Adrienne Edwards The Kiss by Hilton Als Omer Fast My Flesh and Blood by Roy Scranton Conflicts That Alter Our Lives by Kaelen Wilson-Goldie Iraqi Whispers by Sven Lütticken Adrian Ghenie Rememberment of This Past by Mihnea Mircan, Paintings Gags by Suzanne Hudson Adrian Ghenie, Painter of the Twentieth Century by Brigid Doherty Rokni Haerizadeh, Insert
﻿Parkett 99 presents four artists who, with their experience of very different backgrounds, take history (and histories), dreams, the inscrutable, and at times even the disasters in contemporary reality and hold them up to our gaze. Their representations and images capture fleeting, ambivalent, and always unstable realities in kaleidoscopic images, fictitious creations, and shimmering visions, without ever diminishing their truth content. Even if Cao Fei’s art paints a gloomy picture of today’s Chinese megacities, it is regularly illuminated by allegorical flashes of fragile life asserting itself among the rubble. Theaters of war, traumas, and shocking stories from the newsroom seem concentrated through a particular burning glass in Omer Fast’s films, whose credo Kaelen Wilson-Goldie describes as “the disaster and the desire to surpass it, all at once” (p. 121). For author Suzanne Hudson (p. 163), Adrian Ghenie “proposes that one order may cancel another.” Mihnea Mircan considers how Ghenie’s images of decay, as poisonous “bestiaries” from 20th-century history, also contaminate our present (p. 144). It is in the dark color spaces of Lynette Yiadom-Boakye, that a glimmer of hope can be made out. Here Hilton Als finds the fraternity and closeness that in his view are otherwise lacking in contemporary art, as he shares in his engagingly personal essay (p. 86). All of this is fittingly accompanied by the ghosts that appear as recollections of current events in Rokni Haerizadeh’s Insert a- haunting book-within-a- book. (editorial by publisher)
boek
Keywords: Fei, Cao; Yiadom-Boakye, Lynette; Ghenie, Adrian; Fast, Omer